Role of graphene and transition metal dichalcogenides as hole transport layer and counter electrode in solar cells. (11th December 2019) - Iqbal, Muhammad Zahir; Nabi, Jameel‐Un; Siddique, Saman; Awan, Hafiz Taimoor Ahmed; Haider, Syed Shabhi; Sulman, Muhammad
Summary: Photovoltaic (PV) technology got much attention in the past few decades in developing advanced and environment friendly solar cells (SCs). However, high cost, unstable nature, and low efficiency are major limitations towards commercialization of SCs. To overcome the issues, two‐dimensional materials (2DMs) have been exploited due to low cost, high catalytic activity, fast charge separation, and better electrochemical performance. The review emphasis on (a) the electrochemical performance of graphene and transition metal dichalcogenides (TMDCs) as a hole transport layer (HTL) in SCs and (b) to explore low‐cost and effective counter electrode (CE) based on graphene and TMDCs for dye‐sensitized solar cell (DSSC). The review presents a comparative analysis of 2DMs as HTL and CE to attain highly efficient and low‐cost PV devices. Multiple combinations of the material with graphene, graphene oxide (GO), reduced graphene oxide (rGO), tungsten disulfide (WS2 ), molybdenum disulfide (MoS2 ) as HTL, and CE material in PV cells are discussed and comparatively analyzed. Numerous strategies are briefly discussed to enhance the efficiency of SCs by utilizing graphene and TMDCs based HTL and CEs. The review focuses on the recent progress in developing low‐cost and highly efficient PV devices by using 2DMs. Our study reveals that GO/PEDOT:PSS demonstrate a maximum power conversion efficiency (PCE) of 13.1% when fabricated at different revolutions. Moreover, our statistical analysis unveils that efficiency of the cell can be enhanced by optimizing the layer thickness, which provide a route to develop highly efficient and better performance SCs that can be exploited for future commercial applications. Abstract :